Radical childhoods : schooling and the struggle for social change - Gerrard, Jessica (Manchester University Press, 2014)
Education has long been central to the struggle for radical social change. Yet, as social class inequalities sustain and deepen, it is increasingly difficult to conceptualise and understand the possibility for 'emancipatory' education. In 'Radical Childhoods' Jessica Gerrard takes up this challenge by theoretically considering how education might contribute to radical social change, alongside an in-depth comparative historical enquiry.